2018
DOI: 10.1007/s10753-018-0795-6
|View full text |Cite
|
Sign up to set email alerts
|

SPHK-2 Promotes the Particle-Induced Inflammation of RAW264.7 by Maintaining Consistent Expression of TNF-α and IL-6

Abstract: Aseptic implant loosening is a devastating long-term complication of total joint arthroplasty. It is mainly initiated by the interaction of wear debris and macrophages. However, how does the chronic inflammation persist and how to stop it is poorly understood. Sphingosine kinases (SPHKs) are an essential feature of immunosuppressive M2 polarisation in macrophages and a promoter for chronic inflammation. In this study, RAW 264.7 macrophages were exposed to stimulation with titanium particles (0.1 mg/ml), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Qin et al reported that FTY720 is effective in reducing brain inflammation by directing microglia after chronic cerebral hypoperfusion to M2 polarization [47]. FTY720 has been reported to suppress TNFα and IL6 production in RAW264.7 macrophages [48]. The results of the present study are in agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Qin et al reported that FTY720 is effective in reducing brain inflammation by directing microglia after chronic cerebral hypoperfusion to M2 polarization [47]. FTY720 has been reported to suppress TNFα and IL6 production in RAW264.7 macrophages [48]. The results of the present study are in agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that sphingosine kinases/S1P are required for ER and mitochondrial unfolded protein responses and contribute to protection against ER, mitochondrial, and oxidative stress (Lee et al, 2015;Qi et al, 2015;Kim & Sieburth, 2018;Kim & Sieburth, 2019). SPHK2 is required for inflammatory responses in macrophages upon ureteral obstruction and titanium particle stimulation (Ghosh et al, 2018;Yang et al, 2018). It inhibits IL6 production at late time points upon LPS stimulation (Weigert Our studies complement the current knowledge about immune roles of SPHKs by showing that S1P, a product of SPHKs, modulates cytokine responses during stress-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The average diameter of the Ti particles is 3.2 ± 2.7 μm. The Ti particle storage solution is washed with 70% ethanol and autoclaved to remove endotoxins, according to the previously published methods ( Yang et al, 2018 ; Xian et al, 2020 ; Chen et al, 2021 ). After sterility is ensured, the Limulus assistant kit (Xiamen Houshiji, Fujian, China) is used to determine the endotoxin, and endotoxins <0.01 Eu can be used for experiments in vivo and in vitro .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have found that SPHKs are important mediators that regulate the inflammatory response of macrophages induced by wear particles. The upregulation of SPHKs enables macrophages to synthesize and continuously release inflammatory factors, causing local persistent inflammation and immune function damage, eventually leading to loosening of the prosthesis ( Yang et al, 2018 ). SPHK2 generates sphingosine-1-phosphate (S1P) as an isoenzyme ( Hait et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%